EFFECT OF N-ACETYL L -CYSTEINE (NAC) AGAINST OXIDATIVE STRESS - INDUCED NEUROTOXICITY DUE TO LEAD, CADMIUM - B. ANIL KUMAR; A. GOPALA REDDY (International Journal of Pharma and Bio Sciences, 2012)
Lead (Pb) and cadmium (Cd) are potent neurotoxic heavy metals, which induce oxidative stress and membrane disturbances in brain. N Acetyl L cysteine (NAC) is an effective antioxidant and free radical scavenger against oxidative stress. The present study was designed to investigate the neuroprotective efficacy of NAC in protecting the Pb, Cd alone and co exposure induced changes in the activity of acetylcholinesterase (AChE), levels of lipid peroxidation, protein carbonyls, non-enzymatic antioxidants, enzymatic antioxidant status, membrane bound ATPases and histopathology in the brain of rats. To evaluate the neurotoxicity the present study was taken up with a total of 48 rats, divided uniformly into eight groups. The rats of group I and II were kept as control and NAC control @ 300mg/ kg given by oral gavage. Group III, IV and V served as toxic control group viz., lead, cadmium and combination of lead + cadmium @ 1000, 300 and 1000+300 ppm, respectively given in the form of mash feed. Whereas group VI, VII and VIII served as NAC therapeutic groups (lead, cadmium and combination of lead + cadmium @ 1000, 300 and 1000+300 ppm, respectively and NAC @300mg/ kg). The experiment was carried out for 3 months and tissues were collected for antioxidant profile estimation and histopathological study was conducted at the end of the experiment. There was a significant decrease in concentrations of GSH, GST and significant increase in concentration of TBARS, protein carbonyl in the individual and co exposed toxic group and protein carbonyls formation was more significant in co exposed group, as other parameters were appreciably increased, thus represented synergistic effect lies in the co-administration of both metals. Similarly significant decrease in other parameters like Na+K+-ATPase, Mg2+-ATPase, membrane transporter, lipid profile, and neurotransmitters like Ach and Glutamate were noticed. There was a significant alteration in the neurotransmitters in the co exposed group as compared to individual toxic group. Biometals like zinc (Zn) and copper (Cu) did not show any significant correlation with increased accumulation of lead and cadmium in toxic control group. Histopathology of brain revealed vacuolation and degeneration of few areas of cerebral cortex in lead exposed group 3, and mild to moderate degenerative changes and vacuolation in group 4, and lymphoid aggression and degenerative changes in purkinji layer cells in group 5.It concluded that the co existence of these metals showed positive pharmacodynamic interaction and NAC treatment showed significant improvement by replenish GSH pool in the biological system.